Social protection, household size, and its determinants: Evidence from Ethiopia - Hoddinott, John F.; Mekasha, Tseday J. (Taylor and Francis, 2020)
We provide new evidence on the impact of social protection interventions on household size and the factors that cause the household size to change: fertility, child fosterage, and in and out migration related to work and marriage. Using data from an intervention delivered at scale, Ethiopia’s Productive Safety Net Program (PSNP), we find that participation in the PSNP leads to an increase in household size of 0.3 members. We find no evidence that PSNP participation increases fertility and some evidence that fertility is reduced, specifically it reduces the likelihood that an adult female member gives birth by 8.1 percentage points. We reconcile this seemingly divergent findings by showing that the increase in household size arises from an increase in the number of girls aged 12 to 18 years. We present evidence that this occurs because the PSNP causes households to delay marrying out adolescent females.